EFFECTIVENESS OF RFID BASED LIBRARY SYSTEM: SURVEY ANALYSIS - RKAR. Kariapper (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Libraries are one of the significant knowledge repositories apart from e-resources used by people to gain knowledge from different areas. Significant assets of libraries are always books used to obtain data, information, source, and other relevant things necessary for real-world applications. Normally in libraries, books are distributed to the person and collect that book according to the date. Thus, it is required to allocate a well manageable and knowledgeable person in the current field who must manage all kinds of library services without any confusion and error on time. The best solution for overcoming all problems is the Internet of Things (IoT), which gives very accurate and efficient solutions on time with a significantly smaller number of errors. The RFID reader is a device used to gather information from a tag. RFID based library management system is a much better system than a barcode and other traditional library systems. It overcomes almost all problems currently facing in library management. The above conclusion has been drawn by referring and comparing many RFID library systems and the characteristics; and finally, a hybrid RFID library system was proposed in accordance with the number of needy functionalities